2021
DOI: 10.1073/pnas.2107402118
|View full text |Cite|
|
Sign up to set email alerts
|

Health benefits of decreases in on-road transportation emissions in the United States from 2008 to 2017

Abstract: Decades of air pollution regulation have yielded enormous benefits in the United States, but vehicle emissions remain a climate and public health issue. Studies have quantified the vehicle-related fine particulate matter (PM2.5)-attributable mortality but lack the combination of proper counterfactual scenarios, latest epidemiological evidence, and detailed spatial resolution; all needed to assess the benefits of recent emission reductions. We use this combination to assess PM2.5-attributable health benefits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…For calendar year 2016, brake wear and tire wear from light‐duty gasoline and diesel vehicles emitted roughly similar amounts of PM 2.5 as vehicle exhaust on a per‐mile basis, slightly less from motorcycles and light‐duty gasoline trucks, and much less from light‐duty diesel trucks and heavy‐duty diesel vehicles (Bureau of Transportation Statistics, 2021). That said, NO x emissions from vehicle exhaust still contribute relatively more to PM 2.5 ‐related health burdens than primary PM 2.5 emissions from transportation, whether from vehicle exhaust or brake wear and tire wear (Choma et al., 2021; Goodkind et al., 2019). PM 2.5 emissions from the suspension of dust from paved and unpaved roads are included in another source category in the emissions inventory and do not affect our results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For calendar year 2016, brake wear and tire wear from light‐duty gasoline and diesel vehicles emitted roughly similar amounts of PM 2.5 as vehicle exhaust on a per‐mile basis, slightly less from motorcycles and light‐duty gasoline trucks, and much less from light‐duty diesel trucks and heavy‐duty diesel vehicles (Bureau of Transportation Statistics, 2021). That said, NO x emissions from vehicle exhaust still contribute relatively more to PM 2.5 ‐related health burdens than primary PM 2.5 emissions from transportation, whether from vehicle exhaust or brake wear and tire wear (Choma et al., 2021; Goodkind et al., 2019). PM 2.5 emissions from the suspension of dust from paved and unpaved roads are included in another source category in the emissions inventory and do not affect our results.…”
Section: Methodsmentioning
confidence: 99%
“…Other health impact modeling assumptions that bear on results include the effects of population growth and changing baseline mortality rates. In a study of the health benefits associated with reductions in on-road emissions in the US from 2008 to 2017, Choma et al (2021) found that applying 2017 population characteristics to a 2008 emissions scenario increased non-accidental mortality totals by 13% compared to using 2008 population characteristics. Slightly more than half of this increase (6.9%) was due to population growth and the remainder was the result of higher mortality rates, which is due to population aging.…”
Section: Limitations and Advantagesmentioning
confidence: 99%
“…For example, the growing sales of electric vehicles across Europe have resulted in a signi cant drop in CO emissions (Transport & Environment, 2020), meaning fewer human casualties and public health issues and less environmental damage. It is believed that the social bene ts attributed to recent decreases in vehicle CO 2 emissions, particularly in the US, are due to technological innovations by car manufacturers and federal air pollution regulations (Choma et al, 2021). Because electric vehicles can help tackle CO2 emissions, governments across the globe have joined forces to accelerate the adoption of these vehicles under the Electric Vehicles Initiative which is a multi-governmental policy forum established in 2010 (International Energy Agency, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…14 Dedoussi et al (2020) reported that across three years (2005,2011,2018), PM2.5related mortality decrease for road and marine, remains constant for rail, and slightly increase for aviation. 19 Looking at the decreases in on-road transportation emissions in the US from 2008 to 2017, Choma et al (2021) estimated that vehicle-related PM2.5-attributable deaths decrease from 27,700 in 2008 to 19,800 in 2017. 20 Few studies have quantified impacts specifically for freight transportation.…”
Section: Table Of Content Art (Toc Art) 1 Introductionmentioning
confidence: 99%
“…19 Looking at the decreases in on-road transportation emissions in the US from 2008 to 2017, Choma et al (2021) estimated that vehicle-related PM2.5-attributable deaths decrease from 27,700 in 2008 to 19,800 in 2017. 20 Few studies have quantified impacts specifically for freight transportation. Annual PM2.5-related mortality reported by Tessum et al (2019) included 4,250 deaths from combination long-haul truck, 1,550 from combination short-haul truck, 1,480 from diesel-fueled line-haul locomotives, 431 from diesel marine vessels, and 400 from commercial aircraft.…”
Section: Table Of Content Art (Toc Art) 1 Introductionmentioning
confidence: 99%